Wheat production through Utera under rice-wheat cropping system - Deshmukh, K; Baghel, S S; Bhandarkar, A P; Rana, G K (Indian Farming, 2020)
Relay cropping is a method of multiple cropping where one crop is seeded into standing previous crop well before harvesting of the first crop. It may solve a number of conflicts such as inefficient use of available resources, controversies in sowing time, fertilizer application and soil degradation. Relay cropping is a complex suite of different resource efficient technologies, which possesses the capability to improve soil quality, increase net return, increase land equivalent ratio and control the weeds and pest infestation. It is a beneficial tool that results in better utilization of residual soil moisture from previous crops and reduces cost of production per unit area.